Antenna design using particle swarm optimization - Md. , Moniruzzaman; Islam, Md. Rafiqul; Kamaruzzaman , Sopian; Saleem , H. Zaidi (Scientific & Acedemic Publishing, 2011)
This paper presents an optimization technique for microstrip antennas, designed for ambient electro-magnetic energy (AEME) harvesting application, using particle swarm optimization (PSO). Here PSO is applied in multiple levels. Using PSO, two new stripes based microstrip antennas for AEME harvesting application are designed without prior knowledge of patch or ground plane geometry. For multiple levels of PSO, each stripe of the stripes based antenna is divided in many sub-stripes. These sub-stripes are then optimized to improve the antenna performance. Utilizing PSO with single and multiple levels, two separate antennas are designed, evaluated and compared. The stripes based antenna, designed by PSO with single level, provided 96% fractional band width (FBW) at -10 dB return loss. Applying PSO with multiple levels on the same antenna, the FBW was increased to 119%.